Efeitos redistributivos da reforma da previdência - Pedro Herculano Guimar\~aes Ferreira de Souza; Fábio Monteiro Vaz; Luis Henrique Paiva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The discussion around the possible impacts of the recently proposed pension reform (Constitutional Amendment Bill No. 287/2016) on poverty and inequality has been largely impressionistic to date. The present study tries to bridge this gap by using counterfactual microsimulations based on the 2015 National Household Survey (PNAD). These simulations allow for the comparison of poverty and inequality indicators observed in 2015 with estimates for the full implementation of two different versions of the pension reform (the proposed by the Executive and the proposed by the Chamber of Deputies). The effects of implementing the reform are computed both for the overall proposals and for each of their components. Finally, these effects are also estimated on the age structure expected for 2040. The simulations suggest that the pension reform would produce only modest distributive effects. The Executive version would have a larger impact (reaching, directly or indirectly, almost 20 per cent of the Brazilian population). It would increase the poverty rate (based on the -of-the-minimum-wage poverty line) from the current 9.4 per cent to 11.1 per cent. Inequality would increase marginally. The Legislative version would marginally increase the poverty rate (in 0.4 percentage point) and decrease inequality marginally. The results do not support excessively optimistic or pessimistic perceptions about the possible effects of the pension reform on poverty and inequality. -of-the-minimum-wage
Keywords: D31; H31; H55; 330; pension reform; poverty; inequality